An Interprofessional Approach to Teaching Advocacy Skills: Lessons from an Academic Medical–Legal Partnership. Issue 2 (31st October 2020) - Girard, Vicki W.; Moore, Eileen S.; Kessler, Lisa P.; Perry, Deborah; Cannon, Yael
Abstract: Medical students and educators recognize that preparing the next generation of health leaders to address seemingly intractable problems like health disparities should include advocacy training. Opportunities to acquire the knowledge and skills needed to effectively advocate at the policy level to promote systems-, community-, and population-level solutions are a critical component of such training. But formal advocacy training programs that develop and measure such skills are scarce. Even less common are interprofessional advocacy training programs that include legal and policy experts to help medical students learn such skills. This 2016–2017 pilot study started with a legislative advocacy training program for preclinical medical students that was designed to prepare them to meet with Capitol Hill representatives about a health justice issue. The pilot assessed the impact of adding an interprofessional education (IPE) dimension to the program, which in this case involved engaging law faculty and students to help the medical students understand and navigate the federal legislative process and prepare for their meetings. Results from the pilot suggest that adding law and policy experts to advocacy-focused training programs can improve medical students' advocacy knowledge and skills and increase their professional identity as advocates.